Assessment of ESG Integration in Corporate Valuation in GCC Region - Kibria, Md Kaderi; Qazi, Haris Saqib; Damilola Shuaib, Sukaynah Oluwatoyin; Amrullah, Abdulrahim; Nasriddinov, Eradzh (International Journal of Islamic Economics and Governance, 2023)
The concept of Sustainability has been gaining steam in the past few decades in the boardrooms of corporations and regulators in order to decisively address the ecological and social impacts of operations carried by thousands of organizations around the globe. The ESG Score has been established in order to uniformly assess the considerations and effectiveness of initiatives taken by organizations to improve their ecological outlook, or internal relations and interactions among various levels of staff throughout the organizational structure. This paper aims to assess any relationship that may arise between the valuation and capital structure of an organization through assessing the ESG Score, as well as its individual components, namely Environmental, Social and Governance components, upon the Cost of Equity, Cost of Debt, Return on Equity, and Dividend Payout Ratio. The methodology used to observe any correlation between these variables is to conduct OLS regressions between the ESG Score, as well as each of its individual components, with the variables relating to the different methods of valuation, namely the Discounted Cash Flow Model and the Dividend Discount Model. A positive causality was observed between the environmental score and both free cash flow and profitability. Furthermore, we noted a strong association between the overall ESG score and the dividend payout ratio. Further observations were derived from juxtapositions between indices of publicly traded companies ranked based on their ESG performance and companies ranked by their equity, in the markets situated in the United Arab Emirates and the United States. Comparisons were also made between indices assessing the performance of conventional Bonds and Green Bonds.